Hybridization of Alkali Basaltic Magmas: a Case Study of the Ogol Lavas from the Laetoli Area, Crater Highlands (Tanzania). (28th April 2021) - Zaitsev, Anatoly N; Arzamastsev, Andrei A; Marks, Michael A W; Braunger, Simon; Wenzel, Thomas; Spratt, John; Salge, Tobias; Markl, Gregor
Abstract: The southern part of the eastern branch of the East African Rift is characterized by extensive volcanic activity since the late Miocene. In the Crater Highlands, part of the North Tanzanian Divergence zone, effusive and pyroclastic rocks reflect nephelinitic and basaltic compositions that formed between 4·6 and 0·8 Ma. The former are best represented by the Sadiman volcano (4·6–4·0 Ma) and the latter occur in the giant Ngorongoro crater (2·3–2·0 Ma), the Lemagarut volcano (2·4–2·2 Ma) and as a small volcanic field in the Laetoli area (2·3 Ma), where basaltic rocks known as Ogol lavas were erupted through fissures and several cinder cones. Compositionally, they are alkaline basalts with 46·0–47·9 wt% SiO2, 3·0–4·3 wt% of Na2 O + K2 O, Mg# of 61 to 55, and high Cr and Ni content (450–975 and 165–222 ppm respectively). Detailed textural and compositional analysis of the major minerals (olivine, clinopyroxene, plagioclase and spinel-group minerals) reveals the heterogeneity of the rocks. The primary mineral assemblage that crystallized from the Ogol magmas comprises macro- and microcrysts of olivine (Fo89·5–84·2 ), Cr-bearing diopside to augite, magnesiochromite–chromitess, magnetite–ulvöspinelss, andesine–oligoclasess and fluorapatite, with glass of phonolitic composition in the groundmass. All samples contain appreciable proportions of xenocrystic minerals of macro- and microcryst size, with large variations in both concentration and mineral populations between samples. Xenocrysts include olivine with reverse zonation (Fo84·1–72·5 ), rounded and embayed clinopyroxene cores of variable composition, anhedral Cr-free magnetite–ulvöspinelss and embayed oligoclase. These xenocrysts as well as variations in major and trace element contents, 87 Sr/ 86 Sr(i) (0·70377–0·70470) and 143 Nd/ 144 Nd(i) (0·51246–0·51261) ratios provide evidence of multi-stage magma mixing and mingling between Ogol and adjacent Lemagarut volcano basaltic melts with only very minor contamination by Precambrian granite–gneisses. Elevated alkalinity of Ogol lavas, which positively correlates with isotope ratios, and the presence of xenocrystic green core clinopyroxene, perovskite, schorlomite and titanite indicate additional mixing and mingling with evolved nephelinitic magmas and/or assimilation of nephelinitic Laetolil tuffs or foidolitic rocks related to the Sadiman volcano. Owing to their heterogeneity, estimates on the crystallization conditions for the Ogol rocks are difficult. Nevertheless, clinopyroxene–liquid thermobarometry indicates crystallization temperatures of around 1150–1220 °C and records upper-crustal depths of 3–12 km (1–4 kbar). Despite the fact that Ogol basalts are hybrid rocks that formed under open-system conditions with well-documented mixing and mingling processes, they seem to be the best examples closest to primary basaltic melts within the Crater Highlands.